Role of positive psychological strengths and big five personality traits in coping mechanism of University students - Khan, A.; Siraj, Saedah; Lau, P.L. (2011)
Present study aimed to explore the relationship of coping strategies with positive psychological strengths i.e., hope, optimism, self efficacy and resiliency and big-five personality factors among undergraduate university students. Data were collected from 200 students in universities of the Federal Territory Kuala Lumpur, Malaysia. Psychological Capital Questionnaire (Luthans's et al. 2007) [1], Brief Cope Scale (Carver, Scheire & Weintraub, 1989) [2], and Ten-Items Personality Inventory (Swann, Rentfrow, & Gosling, 2003) [3]. were used. Research findings revealed that Positive psychological strengths and Big five personality dimensions were found to be significantly related to coping responses except neuroticism, as persons with high neuroticism were found to be less engage in coping mechanism, while high extraversion, openness and conscientiousness individuals engaged in more problem-focused coping. The results indicate personality factors and PsyCap are emerged as important domains for coping mechanisms.